Beavers as commoners? Invitations to river restoration work in a beavery mode. (27th December 2018) - Woelfle-Erskine, Cleo
Abstract: Community development is related to ecological restoration in several ways. Degraded ecosystems have driven economic decline in communities. Developing institutions for managing and restoring community land bases has long been a strategy in community development. More recently, ecological restoration has been pitched to extraction-dependent communities as part of a 'just transition' to a low carbon economy. In this paper, I think across literatures in geography, ecological restoration and environmental politics to theorize a politics of ecological restoration that resists neoliberal co-optation while supporting Indigenous resurgence. I probe resonance and dissonance among three concepts that have been recently employed to theorize more-than-human relations in the face of extraction, climate change, neoliberal privatization and other Anthropocene phenomena. These concepts are: (1) the commons, one institution for managing land bases as well as an insurgent imaginary of post-capitalist governance; (2) precarity, an idea usually applied in urban settings to describe the late capitalist position of people, usually workers and (3) the more-than-human, an ecologically rooted theoretical perspective that thinks through social dynamics as imbricated with relations among species and entities living together. In my earlier work with a rural settler community trying to restore salmon stream habitats and runs, the idea of a multispecies commons emerged in interviews with residents and restoration workers, and inspired new watershed stewardship practices. Dené scholar Glen Coulthard's critique that commons discourse often erases Indigenous land claims and relations inspired me to think more-than-human commons more deeply, drawing on interviews from beaver-assisted river restoration sites.